2016
DOI: 10.1073/pnas.1601827113
|View full text |Cite
|
Sign up to set email alerts
|

Boosting medical diagnostics by pooling independent judgments

Abstract: Collective intelligence refers to the ability of groups to outperform individual decision makers when solving complex cognitive problems. Despite its potential to revolutionize decision making in a wide range of domains, including medical, economic, and political decision making, at present, little is known about the conditions underlying collective intelligence in real-world contexts. We here focus on two key areas of medical diagnostics, breast and skin cancer detection. Using a simulation study that draws o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
153
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 41 publications
7
153
0
3
Order By: Relevance
“…We have also examined whether neural networks could improve upon the performance of previously proposed heuristics on a skin cancer classification dataset (Kurvers et al, 2016). In the dataset, forty doctors had given their estimations and subjective confidence scores (four point scale) on whether particular patients had malignant melanoma by examining images of their skin lesions.…”
Section: Embracing Complexity: a Machine Learning Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also examined whether neural networks could improve upon the performance of previously proposed heuristics on a skin cancer classification dataset (Kurvers et al, 2016). In the dataset, forty doctors had given their estimations and subjective confidence scores (four point scale) on whether particular patients had malignant melanoma by examining images of their skin lesions.…”
Section: Embracing Complexity: a Machine Learning Approachmentioning
confidence: 99%
“…In the dataset, forty doctors had given their estimations and subjective confidence scores (four point scale) on whether particular patients had malignant melanoma by examining images of their skin lesions. As in Kurvers et al (2016), we used Youden's index as a measure of accuracy, given by J = sensitivity + specificity − 1, with sensitivity defined as the proportion of positive cases correctly evaluated and specificity defined as the proportion of negative cases correctly evaluated. This measure weights equally sensitivity and specificity and it is, thus, insensitive to the unbalances of a dataset (in this case, more cases without cancer than with cancer).…”
Section: Embracing Complexity: a Machine Learning Approachmentioning
confidence: 99%
“…Many studies have shown benefits in combining expert judgments and/ or crowdsourcing nonexpert judgments for a variety of disciplines, including radiology (41,42,44), ophthalmology (73,74), pathology (44,75,76), and clinical predictions (52). However, few studies (41,42,77) have compared the benefits of various pooling algorithms with those predicted by signal detection theory.…”
Section: Simple Majority Voting Obtains Inferior Wisdom Of Crowd Benementioning
confidence: 99%
“…Although some groups seem to have leaders who make decisions alone on behalf of their groups (17,(21)(22)(23), it is difficult for individuals to outperform even simple aggregations of the entire group's individual judgments (4,7,9,10,19,(24)(25)(26). Perhaps that is why humans often make important decisions as a group (27-29), even if the only expedient (30, 31) but effective (24, 31-34) group decision mechanism is to use the simple majority voting rule (35).Previous human studies have shown that combining people's judgments into group decisions can lead to accuracy benefits in various domains, such as estimation (36-38), detection (34,(39)(40)(41)(42)(43)(44), identification (45-47), and prediction (46, 48-52), a phenomenon known as the wisdom of crowds (53). For artificial tasks, where perceptual decisions are limited only by noise that is internal to each observer's brain (i.e., no external noise), the maximum wisdom of crowd benefits are specified by the idealized signal detection theory model that treats observers' internal judgments as normally distributed and statistically independent (SDT-IND) (54).…”
mentioning
confidence: 99%
See 1 more Smart Citation